Preparación y gestión del riesgo de aluviones en el contexto del cambio climático: un estudio en el barrio de La Gasca y en la comuna de Santa Clara de San Millán en Quito - Perin, Arianna (2023)
This thesis addresses the intersection between disaster risk management and community resilience, highlighting its importance in the current context of climate change. The study focuses on the floods that occurred in the La Gasca neighborhood and La Comuna de Santa Clara de San Millán, in Quito, Ecuador. The devastating floods of 2022 and 2024 underscore the growing vulnerability of these areas, driven by uncontrolled urbanization, environmental degradation, and insufficient preventative measures, which exacerbated the impact of these disasters. The study's primary objective is to analyze the institutional actions implemented for disaster risk reduction in these communities and evaluate their level of preparedness for the risk of floods. The research covers the period from 2022 to 2024 and employs a qualitative and ethnographic approach, including semi-structured interviews, focus groups, and participant observation, carried out in 2024. Data collection involved engaging with local communities and institutional representatives, enabling a comprehensive analysis of the policies, interventions, and community perceptions regarding flood risk management. The findings reveal significant gaps in institutional coordination, limited implementation of preventive measures and the lack of community involvement in planning and executing strategies, resulting in insufficient preparation and response capacity during adverse events. In this light, the thesis underscores the urgent need for integrated institutional management that combines disaster risk reduction with climate change adaptation through locally developed plans and a community-centered approach. In fact, the thesis states that current policies remain predominantly reactive, focused on emergency responses rather than addressing the structural drivers of vulnerability. Strengthening community empowerment as active participants in disaster risk governance is identified as a key strategy to bridge institutional efforts with local needs. This is even more important considering the future climate scenario of increasing extreme weather events in Ecuador, especially in the most vulnerable territories, such as some quarters of Quito, exposed to multiple risks. In conclusion, this research provides a detailed assessment of the limitations and opportunities in disaster risk management in two vulnerable Quito neighborhoods in the context of climate change. The results highlight the importance of investing in prevention, fostering community resilience, and designing context-specific and community-based strategies. The study concludes by offering actionable recommendations for enhancing community resilience and underscores the urgency of addressing the intersection of climate change and disaster risk reduction to ensure sustainable urban development and community preparedness and safety.